Sustainable Agricultural Practices as Perceived by Farmers in Sindh Province of Pakistan - Kumbhar, Muhammad Ismail; Sheikh, Saghir Ahmed; Soomro, Aijaz Hussain; Khooharo, Aijaz A. (Journal of Basic & Applied Sciences, 2012)
The study was conducted in Sindh Province of Pakistan. 180 respondents were selected from six district namely Badin, Mirpurkhas, Sanghar Khairpur, Larkana and Jacobabad. From each district 30 respondents were selected by using simple random sampling techniques. This study used a descriptive research design and the target population was farmers. A representative sample of 180 farmers was proposed from six districts of Sindh, namely, 1. Larkana 2. Naushehro Feroze 3. Shaheed Benazirabad 4. Sanghar 5. Mirpurkhas 6. Badin representing the agro-ecological zones of Sindh province producing Cotton, Wheat, Rice, Vegetables, Orchards and Sugar Cane crops. Multistage plan was used to collect the data. A survey questionnaire was designed to collect data for this study. A likert type scale ranging from (1) not familiar (2) to somewhat (3) for very much. This scale was used to asses the level of perceptions of the respondents. The respondents were interviewed personally by well structured and pre-tested direct interview schedule. Questionnaire items were coded and entered into the SPSS computer program. Suitable statistical techniques such as percentage analysis, mean and standard deviation were used to analyze and interpreted the data. The results revealed that out of total growers, majority (54.44%) had medium socio-economic status, whereas 28.89 percent and 16.67 percent had low and high socio-economic status respectively. Extent of knowledge of farmers: Majority of the respondents (52%) were observed in medium category of knowledge followed by high (26.67%) and low (20.56%) levels of knowledge, respectively. It was observed that the farmers were familiar to some what, familiar with sustainable agriculture practices selection of pure seed variety, maintenance and Integrated Soil Fertility, Integrated Weed Management and efficient Use of irrigation water. However the majority of farmers were not familiar with the use of genetically modified Crop, Fish farming, Mulch Technology, EM Technology and IPNMS. However, none of the farmers were found in high category of adoption levels. The respondents suggested adoption of sustainable agriculture practices should be promoted through extension services.